A Toroidal‐Fano‐Resonant Metasurface with Optimal Cross‐Polarization Efficiency and Switchable Nonlinearity in the Near‐Infrared. Issue 21 (19th August 2021) - Hassanfiroozi, Amir; Huang, Po‐Sheng; Huang, Shih‐Hsiu; Lin, Kuang‐I; Lin, Yu‐Tsung; Chien, Chien‐Feng; Shi, Yuzhi; Lee, Wen‐Jen; Wu, Pin Chieh
Abstract: The recent progress in plasmonic metasurfaces gives rise to an intense evolution of controlling light properties such as phase, amplitude, polarization, and frequency. In this work, a new paradigm is established to control the light properties centered on low‐loss toroidal multipoles with high field enhancement in contrast to most of the previous plasmonic metasurfaces that are optimized through electric and magnetic multipolar resonances. Through a proof‐of‐concept demonstration, a linear cross‐polarization conversion efficiency reaching 22.9%, remarked as the optimal value that can exist in a single‐layer plasmonic metasurface in the near‐infrared spectrum, is experimentally realized. A polarization‐insensitive toroidal response, that previously was accessible only in isotropic high‐index metasurfaces, is also observed. Furthermore, a giant anisotropic (polarization‐sensitive) generation of the second‐harmonic frequency is demonstrated with the proposed polarization‐independent toroidal metasurface that provides different levels of electric energy storage within the metasurface. These findings open a new path for keeping low‐efficiency plasmonic components on track when one engineers a metasurface based on the toroidal multipole family. Abstract : This work establishes a paradigm to control the light properties centered on low‐loss toroidal multipoles. Through a proof‐of‐concept demonstration, a linear cross‐polarization conversion with the efficiency of 22.9% in the realm of toroidal dipole–quadrupole coupling is experimentally realized. Furthermore, the proposed polarization‐independent toroidal metasurface demonstrates a giant anisotropic generation of the second‐harmonic frequency.